Pengaruh Penggunaan Metode Jarimatika Terhadap Kemampuan Berhitung Perkalian Anak Usia Sekolah Dasar - Neng Dewi Anggraeny; Siti Masyithoh (Elementar : Jurnal Pendidikan Dasar, 2022)
The purpose of this study was to find out and describe how the effect of the application of the Jarimatika method on the multiplication ability of high-grade students. The research method used is descriptive quantitative with data collection techniques using data recording with permanent products. Data retrieval using data recording with permanent products, observation and documentation with the research sample consisting of one student aged 4th grade. Data analysis used visual analysis method which consisted of visual analysis of graphs, analysis under conditions and analysis between conditions. The results of this study indicate that the multiplication arithmetic ability of students during the four phases is affected by the use of the Jarimatika method. This can be seen from the results obtained in the Baseline 1 phase, students got the highest score = 40, the Intervention phase 1 = 80, the Baseline 2 phase = 80, and the Intervention phase 2 = 100. The ability of students to count multiplications in the baseline phase is sufficient. good, in the intervention phase very good.